Optimalisasi Kesehatan Mental Orang Tua & Anak Usia Dini Melalui Psikoedukasi Gerakan Rumah Ramah Anak pada Masyarakat Gili Iyang Kabupaten Sumenep - Nawangsari, Nur Ainy Fardana; Surjaningrum, Endang Retno; Suminar, Dewi Retno; Herdiana, Ike; Tappi, Melisa Nurcahya; Khawarizmi, Arif Rahman; Palupi, Listyati Setyo (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2025)
This research aims to optimise the mental health of parents and early childhood in Gili Iyang, Sumenep, through psychoeducation for the ‘Child Friendly Home’ movement. The programme uses psychoeducation and joyful learning methods to increase parents' motivation and positive attitudes in creating a nurturing environment that supports children's development. The participants were 50 parents, children, and early childhood educators from Bancamara and Banraas villages. Participants were selected by purposive sampling, based on the purpose of the activity, which is to optimise the mental health of parents and early childhood. The results of the pretest and posttest evaluations showed a significant increase in knowledge with a note that there was a need for re-evaluation in the preparation of the questions. However, through observation, discussion, and question and answer, positive attitudinal changes related to child-friendly parenting were observed. These findings indicate the importance of community-based interventions to improve family mental health in rural areas. This study recommends that further development is needed so that similar programmes can be implemented in other communities.